Building a Clean Machine : Anti-Corruption Coalitions and Sustainable Reform - Johnston, Michael, 1949- 1949- (The World Bank, 2005)
Ghana's Anti-Corruption Coalition, and the Bangalore Agenda Task Force in Bangalore, Karnataka State, India. In Part III the authors link those cases to a broader analysis, suggesting that while purposive incentives are common in the early phases of all coalitions, other varieties must be added to the mix. Wilson's scheme points to ways in which the imaginative use of incentives can aid the transition from one phase of coalition development to the next. The authors conclude with general strategic issues, suggesting ways in which their analysis can be applied to those questions given the important variations to be found among cases. This paper—a product of the Governance, Finance, and Regulation Division, World Bank Institute—is part of a larger effort in the institute to address governance and anti-corruption issues in developing countries